CHARACTERISTICS OF THE GENERAL ANTHOLOGY OF POETS OF THE XVIII THE CENTURY (ON THE EXAMPLE OF THE INDIAN LITERARY ENVIRONMENT) (Scientific journal of the Fergana State University, 2024)
Anthologies of the XVIIIth century are considered valuable major written monuments in the literary criticism of Persian-Tajik literature and serve as both a reliable and significant source in the study of the literary history of this period.The article states that the anthology developed primarily as a valuable source providing accurate and reliable information about the life and work of poets. Along with the harmony and similarity of the components of general anthologies of the XVIIIth century, it is explored that each of them was created with its own unique characteristics. The study of the anthology of this period indicates that literature and literary criticism are not only a source that reveals problems, but also a valuable source that explores and illuminates historical, cultural, social and moral issues.